Relationship between Body Condition Score and Milk Production Parameters in Murrah Buffaloes: An Observational Study - A. Anitha (New Visions in Biological Science Vol. 7, 2021)
A study was carried out to assess the influence of BCS on milk production parameters of lactating Murrah buffaloes. India is the origin for the best buffalo breeds and Murrah buffalo is the highest milk producing buffalo breed in the world. The postpartum changes in Body Condition Score (BCS) studied from calving to four months of lactation in 40 Murrah buffaloes showed that BCS decreased from calving to two months of lactation and then gradually increased. Significant (P < 0.05) inverse relationship (r = -0.96) was observed between BCS and milk yield. The effect of BCS at calving (BCSc) on the milk production parameters were studied in 40 Murrah buffaloes divided into 4 groups of 10 buffaloes each based on BCSc (G1 – 2.5 to 2.99, G2- 3.0 to 3.49, G3- 3.5to 3.99 and G4- 4.0 to4.49). The total milk production (kg) upto 4 months of lactation, peak milk yield (kg), persistence, milk fat per cent, milk protein per cent and SNF per cent were 1030.93, 9.50, 1.65, 6.44, 3.39 and 8.99, respectively for G1 group, 1197.12, 11.60, 1.69, 7.54, 3.74 and 9.34 respectively for G2 group, 1658.67,16.50,1.77,8.62, 4.24 and 9.84, respectively for G3 and 1359.92, 13.75, 1.68, 9.37, 3.97 and 9.57, respectively for G4 group. Buffaloes of G3 group had significantly (p<0.01) more milk yield, peak milk yield, milk protein and SNF compared to the other groups where as buffaloes of G4 group had significantly (P<0.01) more milk fat.